Atomically dispersed cobalt trifunctional electrocatalysts with tailored coordination environment for flexible rechargeable Zn–air battery and self-driven water splitting - Zhang, Zheye (2021)
Designing multifunctional catalysts with high activity, stability, and low-cost for energy storage and conversion is a significant challenge. Herein, a trifunctional electrocatalyst is synthesized by anchoring individually dispersed Co atoms on N and S codoped hollow carbon spheres (CoSA/N,S-HCS), which exhibits outstanding catalytic activity and stability for the oxygen reduction reaction, oxygen evolution reaction, and hydrogen evolution reaction. When equipped in liquid or flexible solid-state rechargeable Zn–air batteries, CoSA/N,S-HCS endows them with high power and energy density as well as excellent long-term cycling stability, outperforming benchmark batteries based on a commercial Pt/C + RuO dual catalyst system. Furthermore, a self-driven water splitting system powered by flexible Zn–air batteries is demonstrated using CoSA/N,S-HCS as the sole catalyst, giving a high H2 evolution rate of 184 µmol/h. The state-of-art experimental characterizations and theoretical calculations reveal synergistic cooperation between atomically dispersed Co-N active sites, nearby electron-donating S dopants, and the unique carbon support to single-atom catalysts (SACs). This work demonstrates a general strategy to design various multifunctional SAC systems with a tailored coordination environment.